An Exposed KID-Like Domain in Human T-Cell Lymphotropic Virus Type 1 Tax Is Responsible for the Recruitment of Coactivators CBP/p300 - Harrod, Robert (American Society for Microbiology, 1998)
Human T-cell lymphotropic virus type 1 (HTLV-1) transcriptional activation is mediated by the viral transactivator, Tax, and three 21-bp repeats (Tax response element [TxRE]) located in the U3 region of the viral long terminal repeat (LTR). Each TxRE contains a core cyclic AMP response element (CRE) flanked by 5′ G-rich and 3′ C-rich sequences. The TxRE binds CREB (CRE-binding protein) and Tax to form a ternary complex and confers Tax-dependent transactivation. Recent data indicate that Tax functions as a specific link to connect CREB-binding protein (CBP)/p300 in a phosphorylation-independent manner to CREB/ATF-1 assembled on the viral 21-bp repeats. Glutathione S-transferase pull-down performed with Tax deletion mutants and peptide competition have localized the site in Tax critical for binding CBP/p300 to a highly protease-sensitive region around amino acid residues 81 to 95 ((81)QRTSKTLKVLTPPIT(95)) which lies between the domains previously proposed to be important for CREB binding and Tax subunit dimerization. Amino acid residues around the trypsin- and chymotrypsin-sensitive sites ((88)KVL(90)) of Tax bear resemblance to those in the kinase-inducible domain of CREB ((129)SRRPSYRKILNE(140)) surrounding Ser-133, which undergoes signal-induced phosphorylation to recruit CBP/p300. Site-directed mutagenesis of residues in this domain (R82A, K85A, K88A, and V89A) resulted in proteins which failed to transactivate from the HTLV-1 LTR in vivo. These mutants (K85A, K88A, and V89A) bind CREB with similar affinities as wild-type Tax, yet interaction with CBP/p300 is abrogated in various biochemical assays, indicating that the recruitment of CBP/p300 is crucial for Tax transactivation. A Tax mutant, M47, defective in the COOH-terminal transactivation domain, continued to interact with CBP/p300, suggesting that interactions with additional cellular factors are required for proper Tax function.